Estudio de las características estáticas y dinámicas de los actuadores Electromecánicos (EMA) con GUI de MATLAB (2022)
The element simulation process is nowadays one of the most important means to evaluate possible performances in the operation of almost any object, for this reason the finite element analysis (FEM) and the finite difference method (FDM) are important for find out the transient response results, for this purpose MATLAB-Simulink is used to design actuators such as electromagnetic valves.